Marchés immobiliers résidentiels et étalement urbain contraint - Olivier Dubois; Jean-Marie Halleux (Belgeo)
The release of mobility constraints has facilitated urban sprawl, i.e. the increasing spatial dissociation between urban cores and implantation sites of households and economic activities. The aim of this paper about the Walloon part of the Brussels metropolitan region is to analyse how housing market constraints reinforce the trend towards residential sprawl. Based on an analysis of the financial accessibility to both, the market for new housings and the market for pre-existing housings, it is here the influence of the price level decreasing with the distance from Brussels which is taken into account. Due to their limited financial resources and to this price gradient, many households are obliged to settle on remote sites in order to acquire their property goods. In relation to this phenomenon, it appears that, from a spatial as well as from a social point of view, the Brussels urban system is not able to settle the metropolitan growth on an adapted way. Indeed, new residential locations reinforce the increasing dissociation between work places and living places, which leads to a useless increase in mobility costs as well as a serious accentuation of socio-spatial segregations.